IMPROVING BALANCE STABILITY THROUGH APPLICATION OF TRAINING PROGRAM IN STRESSFUL CONDITIONS VIA VIRTUAL REALITY GLASSES AND GLASSES SIMULATING ALCOHOL USE - Vladimir Angelov (Scientific Publishing House. NSA Press, 2018)
The aim of this study was to investigate the effect of using difficult conditions in the balance training program through virtual reality glasses and glasses simulating alcohol consumption. According to the hypotheses of the study, the application of the balance training program with applying additional difficulty on the vestibular apparatus through technical means will lead to a greater training effect. The object of the study was the balance stability. The research was done among twenty-six Bulgarian students from the National Sports Academy. A pedagogical experiment was conducted to prove the hypothesis of the study. The testing session included two balance exercises. The collected data from the study were statistically processed with the variance analysis and t-criterion of Student. The results of the research were statistically significant and showed a greater increase in the parameters of the experimental group (FE: 33,3c/o; P=100c/o; SE: 14,3c/o; P=99,9c/o) than in those of the control group (FE: 14,7c/o; P=99,9c/o; SE: 8,3c/o; P=99,9c/o). The analysis of the results justified the hypothesis of the research. The study found out that the usage of the balance training program that applies additional difficulty on the vestibular apparatus through virtual reality glasses and glasses simulating alcohol use leads to a better balance stability.